THU0467 Efficacy and patency of revascularisation in patients with thromboangiitis obliterans (BUERGER'S DISEASE). (12th June 2018) - Mirault, T.; Delahaye, M.; Galloula, A.; Guillet, M.; Zarka, S.; Courtois, M.-C.; Sapoval, M.; Goudot, G.; Messas, E.
Abstract : Background: The cornerstone of therapy in thromboangiitis obliterans (TAO) is complete abstinence from tobacco. In addition to discontinuation of cigarette smoking, very few pharmacological and surgical options of controversial efficacy are available to date. TAO is associated with a high amputation rate because of tobacco continuation, medical therapy failure, and desert foot with no revascularisation option. Endovascular or bypass revascularisation patency and efficacy are poorly described in the literature. Objectives: To describe the results of the French National Reference Centre on TAO on revascularisation modalities, their patency and efficacy. Methods: Among the 198 patients followed in our centre, we retrieved data from 19 patients for who a revascularisation procedure has been attempted. Patency was assessed on angioCT scan and Duplex ultrasounds performed during follow-up. Efficacy was assessed according to clinicians in charge of the patient, and if an amputation had been performed or not despite a primary successful procedure. Results: In this cohort of 19 patients, 16 were male (84%), all were tobacco active users, and 21% cannabis users. Median follow-up was 19.9 months [11.0–36.9]. Iloprost infusion had been tested for 84.2% of the patients before revascularisation, and 63.2% had a dihydropiridine, 73.3% a statin and 100% at least aspirin. Endovascular procedure was exclusive for 14 patients, and bypass surgery for 1 patient. Four patients had combined procedures. Globally, 44 procedures including 7 bypasses (15.9%) and 37 endovascular surgeries (84.1%), due to multiple procedures for some patients. Primary patency of endovascular procedures was 89.4% and their patency duration was 221±173 days. For bypass surgery, the patency duration was higher 827±408 days (p=0.273). Looking at the territory, aorto-iliac revascularizations gave better results on long term 1830 days followed by upper limb 751±402 days, femoro-popliteal procedures 347±196 days and finally infra-popliteal ones with 178±134 days. Stability or improvement was observed after 52.3% of the revascularizations. Among the failures, 21.2% were associated with a minor amputation, and 11.3% with a major amputation. No predicting factors of failure could have been determined. Conclusions: We report the largest series of revascuarization in TAO. As expected, proximal artery revascularisation of lower limbs were associated with a higher and a longer patency rate than femoro-popliteal procedures and even more than infra-popliteal revascularisations. Suprinsingly, upper limb revascularisation had a better outcome than for lower limbs. Efficacy of revascularizations are difficult to assess because such procedures are often proposed as a salvage option. However, it is worth to note that more than 50% of the patients had a benefit from the revascularisation. Disclosure of Interest: T. Mirault Grant/research support from: GENZYME (2010) M. Delahaye: None declared, A. Galloula: None declared, M. Guillet: None declared, S. Zarka: None declared, M.-C. Courtois: None declared, M. Sapoval: None declared, G. Goudot: None declared, E. Messas: None declared